Nutrition Screening and Assessment in Hospitalized Patients: A Survey of Current Practice in the United States. (August 2014) - Patel, Vihas; Romano, Michelle; Corkins, Mark R.; DiMaria-Ghalili, Rose Ann; Earthman, Carrie; Malone, Ainsley; Miller, Sarah; Sabino, Kim; Wooley, Jennifer; Guenter, Peggi; ,
Background : The Joint Commission has mandated universal screening and assessment of hospitalized patients for malnutrition since 1995. Although various validated and nonvalidated tools are available, implementation of this mandate has not been well characterized. We report results of a survey of hospital-based professionals in the United States describing their perspective on the current range of nutrition screening and assessment practices as well as associated gaps in knowledge. Methods and Materials : Data from a 2012–2013 cross-sectional, web-based survey targeting members of the American Society for Parenteral and Enteral Nutrition (A.S.P.E.N.), the Academy of Medical-Surgical Nurses, and the Society of Hospital Medicine were collected with non–hospital-based members excluded. Descriptive statistical analysis was performed. Results : Survey data from 1777 unique email addresses are included in this report. A majority of respondents were dietitians, nearly half were A.S.P.E.N. members, and 69.4% reported caring for a mix of adult and pediatric patients. Most respondents answered affirmatively about nutrition screening being performed in alignment with The Joint Commission mandate, but only 50% were familiar with the 2012 Consensus Statement from the Academy of Nutrition and Dietetics/A.S.P.E.N. on adult malnutrition. In most cases, nurses were primarily responsible for nutrition screening, while dietitians had primary responsibility for assessment. No one specific assessment tool or International Classification of Diseases, Ninth Revision code was identified as being used a majority of the time in assessing or coding a patient for malnutrition. Conclusions : The survey findings affirmed compliance with accreditation standards in completing a nutrition screen within 24 hours of admission, and most hospitals appear to have a process to perform a nutrition assessment once a screen is completed. However, there is considerable heterogeneity in both use of tools and mechanisms for coding capture. Opportunities exist to improve education around nutrition screening and assessment and to identify ideal practices for these processes in hospitalized patients.